In vitro and in vivo effects of Pelargonium sidoides DC. root extract EPs® 7630 and selected constituents against SARS-CoV-2 B.1, Delta AY.4/AY.117 and Omicron BA.2 - Jackson Emanuel; Jackson Emanuel; Jan Papies; Jan Papies; Celine Galander; Celine Galander; Julia M. Adler; Nicolas Heinemann; Nicolas Heinemann; Kathrin Eschke; Sophie Merz; Hannah Pischon; et al. (Frontiers Media S.A., 2023)
The occurrence of immune-evasive SARS-CoV-2 strains emphasizes the importance to search for broad-acting antiviral compounds. Our previous in vitro study showed that Pelargonium sidoides DC. root extract EPs® 7630 has combined antiviral and immunomodulatory properties in SARS-CoV-2-infected human lung cells. Here we assessed in vivo effects of EPs® 7630 in SARS-CoV-2-infected hamsters, and investigated properties of EPs® 7630 and its functionally relevant constituents in context of phenotypically distinct SARS-CoV-2 variants. We show that EPs® 7630 reduced viral load early in the course of infection and displayed significant immunomodulatory properties positively modulating disease progression in hamsters. In addition, we find that EPs® 7630 differentially inhibits SARS-CoV-2 variants in nasal and bronchial human airway epithelial cells. Antiviral effects were more pronounced against Omicron BA.2 compared to B.1 and Delta, the latter two preferring TMPRSS2-mediated fusion with the plasma membrane for cell entry instead of receptor-mediated low pH-dependent endocytosis. By using SARS-CoV-2 Spike VSV-based pseudo particles (VSVpp), we confirm higher EPs® 7630 activity against Omicron Spike-VSVpp, which seems independent of the serine protease TMPRSS2, suggesting that EPs® 7630 targets endosomal entry. We identify at least two molecular constituents of EPs® 7630, i.e., (−)-epigallocatechin and taxifolin with antiviral effects on SARS-CoV-2 replication and cell entry. In summary, our study shows that EPs® 7630 ameliorates disease outcome in SARS-CoV-2-infected hamsters and has enhanced activity against Omicron, apparently by limiting late endosomal SARS-CoV-2 entry.